Synthesis of norpandamarilactonines, pandamarilactonines, and pandanamine - Gogoi, Sanjib; N. P. Argade (Synthesis-Stuttgart, 2008)
A facile route to naturally occurring (+/-)-norpandamarilactonines A and B, (+/-)-pandamarilactonines A-D, and pandanamine has been described from 3-methylfuran-2(5H)-one, with a reductive intramolecular aza-Michael-type addition as the key step.
Keywords: 3-methylfuran-2(5H)-one; condensation; intramolecular aza-Michael reaction; pandamarilactonines